Global marketing - Johansson, Johny K. (Irwin/McGraw-Hill, 2000)
GLOBAL MARKETING: Foreign Entry, Local Marketing, and Global Management can be used at the better undergraduate programs where the students have had some exposure to global management or global business or in the MBA curriculum. The subtitle for this text is an important way to remember what makes this book distinct. This text offers a three-pronged approach to Global Marketing. That approach is Foreign Entry, Local Marketing, and Global Management and this represents the structure for the text. Johansson addresses how you market an existing product in new global markets and also discusses how a company develops a new product for a global market. This discussion takes into consideration the culture and needs of those customers. Most International Marketing books have a separate chapter for each of the environments (legal and regulatory, political, Business Customs, etc) and then they launch into a discussion of marketing management for global markets. However, Johansson only has a separate chapter on culture and then he integrates the rest of the environment discussions throughout the text and where appropriate. This too is a distinct feature of the text